ALGORITMA FxAFA LANGKAH ADAPTASI DINAMIS UNTUK PENGHAPUSAN DERAU - Taufiq, Arif Johar; Tamam, M. Taufiq (Sainteks, 2012)
In the present study has addressed the application of noise canceling FxAFA using dynamic step size algorithm, and we got the result that the noise reduction of FxAFA dynamic step size algorithms better then FxAFA algorithm. But when Compared with the noise reduction to FxLMS algorithms, FxLMS still better than the FxAFA dynamic step size algorithm. Based on the data from the computer simulation results of noise reduction FxLMS = 27.6793 dB, FxAFA dynamic step size and FxAFA db = 26.0329 = 23.6059 dB. Keywords: FxAFA, FxAFA dynamic adaptation measures, noise removal